Enhancement of the digestion of virgin silkworm pupae oil (bombyx mori) by forming a two-layer emulsion using lecithin and whey protein isolate - Yooying, Ratchadaporn; Tangsanthatkun, Janjira; Tan, Chin Ping; Klinkesorn, Utai; Harnsilawat, Thepkunya; Peanparkdee, Methavee (Springer, 2022)
Virgin silkworm pupae oil is a safe oil source that is nutritionally equivalent to commonly used vegetable oils and is a novel source of ±-linolenic acid (18:3 n-3). In terms of health benefits, this substance can be added to food products for n-3 fatty acid fortification. Emulsification is a well-known encapsulation technique that has been widely used to deliver healthy and essential fatty acids in foods and beverages and enhance the bioavailability or bioactivity of lipophilic active compounds during gastrointestinal (GI) digestion. This study evaluated the influence of whey protein isolate (WPI) on the physical and chemical properties of lecithin-stabilized silkworm pupae-oil-in-water emulsions at different concentrations. Results showed that the physical stability of emulsions increased with the WPI concentration. The two-layer emulsions stabilized using lecithin“WPI at 4.0 wt were stable as evidenced by the small particle size (~ 0.4 ¼m), monomodal distribution (Polydispersity Index < 0.3), and without phase separation after 24 h. Additionally, it also provided faster and higher release of free fatty acid (108.05) with greater value of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity during intestinal digestion. The findings of this study showed that the two-layer emulsion stabilized with lecithin“WPI has good physical characteristics and high stability during simulated GI digestion, which may have beneficial implications for further functional food applications.